THE ROLE AND PLACE OF SMALL ENTREPRENEURSHIP IN THE STRUCTURE OF THE ECONOMY OF UKRAINE - ANHELKO, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article highlights the role and place of small entrepreneurship in the economy of Ukraine through the prism of defining and evaluating the functions and tasks performed by it. Attention is focused on the main functions and tasks of small entrepreneurship. It was determined that small entrepreneurship plays an important role in weakening monopoly and developing competition, determining the pace of economic development, ensuring the saturation of the market with consumer goods and services of daily demand, implementing innovations. It was found that small entrepreneurship makes a significant contribution to solving a number of socio-economic problems, in particular employment and unemployment. It is noted that the importance and place of small entrepreneurship in the socio-economic and political life of society can be determined not only by the functions performed by it, but also based on the assessment of integrated indicators. With the help of evaluation of integrated indicators of activities of small business entities, the positive development of the latter has been established. It is emphasized that today, in the conditions of a full-scale war between Russia and Ukraine, subjects of small entrepreneurship, as well as medium and large ones, are affected by military actions in various ways, including depending on their location. It is important to understand that despite the difficult operating conditions, the role and place of small entrepreneurship in the structure of the national economy is not only increasing, but is necessary and important. Small entrepreneurship plays a decisive role in supporting and restoring the national economy of Ukraine in the post-war period.
Keywords: small entrepreneurship; microentrepreneurship; subjects of small entrepreneurship